Risk Factors of Acute Otitis Media in Early Age (A Meta-Analysis) - Ishfaq Ahmed, Akhtar Ali Lakhiar, Sajjad Yousuf, Amrat Kumar, Muhammad Asif Ashraf, Abid Rafique Chaudhry, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The purpose of this study is to evaluate the risk factors of acute otitis media in children. Study Design: Case Control study Place and Duration: Conducted at Bilawal medical Hospital Kotri, LUMHS Jamshoro, during from the period August 2021 to January 2022. Methods: There were 110 children with ages 1 month to 6 years were presented in this study. After obtaining informed written permission, a mother's age, parity, gestational age, and smoking history were documented in detail for each of the instances described. Patient’s clinical presentation were also recorded. All the patients had confirmed acute otitis media. Risk factors of AOM among enrolled cases were recorded. SPSS 21.0 was used to analyze complete data. Results: Among 110 children, there were 65 (60.2%) males and 43 (39.8%) females. We found that majority of the cases 42 (38.2%) were aged between 1month to 2-years had AOM.Symptoms included fever, otalgia, otorrhea, restlessness, nausea, vomiting, hearing loss, and tinnitus or vertigo in individuals. Tobacco usage by the parents, premature birth, supine bottle feeding, pacifier use, and day care attendance were all significant risk factors for acute otitis media (AOM). The current investigation showed no link between AOM and a craniofacial abnormality. Conclusion:We found that bottle feeding,day care attendance during the first 10 months of life, supine bottle feeding, pacifier usage in the second 6 months of life, parental cigarette smoking, preterm infant, and allergy were significant risk factors for AOM.